Pitching for Finance for a Business Start-Up: a Case Study of IviewCameras - Molian, David (Senate Hall, 2007)
In September 2002 Pete Rankin is leaving his MBA programme to launch a new internet-based venture, IViewCameras. The price of wireless CCTV (closed-circuit TV) has fallen dramatically, creating a new market opportunity. To launch his venture, Pete has reached agreement with an established internet-based retailer, Internet Cameras Direct, to incubate IviewCameras in return for shares. Internet Cameras Direct can provide IViewCameras with an existing infrastructure for sales, procurement and fulfilment. However, Pete's presentation of his venture to external reviewers has gone badly. A venture capitalist doubts whether a business model that proposes both to sell manufacturers' brands and build an IviewCameras' brand is viable, and questions whether the business is truly sustainable without an intellectual property base. Pete is left to ponder whether the concept is fatally flawed, or whether he should fall back on his self-belief and instinct that this is the right product at the right time. The case examines the issues of: low-cost market entry via business incubation; what sort of market research is required to satisfy external investors at start-up; and whether an internet-based start-up needs intellectual property to sustain its business model. The central area for class discussion is how to evaluate a business proposition, and the credibility of the entrepreneur, in an emerging market space.
Keywords: entrepreneurship|market entry|new ventures|dotcoms|start-up|internet retailing